Multi-functional code for hydrogen isotopes transport analyses: verification & validation against fusion-relevant applications - F. Hattab; V. Narcisi; C. Ciurluini; A. Trotta; A. Santucci; F. Giannetti (Nuclear Fusion)
The management of hydrogen isotopes within a fusion reactor remains a key design issue, with many constraints concerning tritium. The fusion power plant should be self-sufficient with respect to its fuel, while the contamination of components and the releases outside the primary system should be limited. There is a need for versatile numerical tools to assess tritium inventories and losses, which will support the design of components relevant to tritium management and inform mitigation strategies. This work presents the development, verification and validation of the System-level Application for Engineering Tritium Transport Analysis ( SAETTA ). SAETTA is a modular, system-level code designed with flexibility in mind. It is capable of simulating thin membranes as well as large systems with several components and connections. The program is built using Python, with a one-dimensional approach to simulate the transport of hydrogen isotopes in fluid and solid systems. Various factors influencing the transport of hydrogen isotopes are addressed, such as chemical reactions, mass transfer in the fluid, surface effects, permeation, trapping, leakage and decay. SAETTA methodology and implementation strategy are thoroughly outlined. In addition, a comprehensive verification and validation campaign has been specifically designed and performed to demonstrate the code capabilities in a wide range of fusion-related applications.